Okręg Polskiego Towarzystwa Turystyczno-Krajoznawczego w Bydgoszczy w latach 1951-1975. Cz. 2. Działalność programowa (Kronika Bydgoska, 2010)
The article is about the activity of the PTTK Polish Tourist Country-Lovers’ Society District Board in Bydgoszcz. PTTK was establishcd in 1951 as a result of the merger of the PTT Polish Tatra Society, the PTK Polish Sightseeing Society, and tourist sections of several other sports associations in December 1950. The PTTK District Board in Bydgoszcz was established on March 4, 1951. The board functioned as the representative body co-ordi- nating and supervising the society’s program-statutory operations in the region. It continued the operations of the Voivodeship Board of the PTK Pomeranian District seated in Toruń, active starting from March 23, 1930 in Pomorskie Voivodeship. The article presents the society’s program operations, development of its organisational structures, tourist base in the voivodeship, co-operation with the region’s authorities, and contacts with school and academic youth. The society’s new field of activity, i.e. foreign tourism, is presented as well.